Five factor model personality traits relate to adult attention-deficit/hyperactivity disorder but not to their distinct neurocognitive profiles. (December 2017) - Van Dijk, Fiona E.; Mostert, Jeannette; Glennon, Jeffrey; Onnink, Marten; Dammers, Janneke; Vasquez, Alejandro Arias; Kan, Cornelis; Verkes, Robbert Jan; Hoogman, Martine; Franke, Barbara; Buitelaar, Jan K.
Abstract: Deficits in multiple neuropsychological domains and specific personality profiles have been observed in attention-deficit/hyperactivity disorder (ADHD). In this study we investigated whether personality traits are related to neurocognitive profiles in adults with ADHD. Neuropsychological performance and Five Factor Model (FFM) personality traits were measured in adults with ADHD (n = 133) and healthy controls (n = 132). Three neuropsychological profiles, derived from previous community detection analyses, were investigated for personality trait differences. Irrespective of cognitive profile, participants with ADHD showed significantly higher Neuroticism and lower Extraversion, Agreeableness, and Conscientiousness than healthy controls. Only the FFM personality factor Openness differed significantly between the three profiles. Higher Openness was more common in those with aberrant attention and inhibition than those with increased delay discounting and atypical working memory / verbal fluency. The results suggest that the personality trait Openness, but not any other FFM factor, is linked to neurocognitive profiles in ADHD. ADHD symptoms rather than profiles of cognitive impairment have associations with personality traits. Highlights: The Five Factor Model personality trait Openness, but not any other FFM factor, is linked to neurocognitive profiles in ADHD. ADHD subjects showed higher Neuroticism and lower Extraversion, Agreeableness, and Conscientiousness than healthy controls. The presence of ADHD rather than cognitive profile is associated with personality traits.